Estimating the Costs of PrEP (Pre-Exposure Prophylaxis) HIV among Men who Have Sex with Men (MSM) Population as Advanced Preventive Strategies: The Societal Perspective - Belawati Yeny Ristaning; Febrinasari Ratih Puspita; Widyaningsih Vitri; Probandari Ari (BIO Web of Conferences)
Men who have sex with men (MSM) are the key population that dominates the new HIV incidence rate in Indonesia. WHO recommends the use of Pre-Exposure Prophylaxis (PrEP) HIV as an advanced preventive strategy. This study aimed to estimate the total cost of PrEP in one year from a societal perspective. Observational research with a retrospective approach was conducted on the MSM population in Solo Raya, Central Java, Indonesia. Data were collected through a questionnaire to get direct nonmedical and indirect cost data. Direct medical costs were estimated from the tariff regulations. The result showed that, from 50 MSM, the mean age was 26.78 years, 10% had comorbidity, 26% had a sexually transmitted infection (STI) history and 72% had high-risk sexual behavior. The average estimated cost of a PrEP per person was $328.44. Direct medical costs were the biggest proportion of the total estimated cost. From the sensitivity analysis, the total estimated cost was the most sensitive to risk factor parameters. The risk factors, which include STI history and high-risk sexual behavior, have the greatest influence on the total cost because of the increased number of visits. PrEP implementation must involve other promotional and preventive strategies to reduce risk factors.